Quality assurance in trichiasis surgery: a methodology. Issue 3 (29th September 2010) - Buchan, John C; Limburg, Hans; Burton, Matthew J
Abstract : Background: Trachoma remains a significant cause of blindness in many parts of the world. The major route to blindness involves upper lid entropion leading to trachomatous trichiasis (TT), which promotes progressive corneal opacification. The provision of surgery to correct TT in the populations most severely affected is a major challenge for the global effort to eliminate trachoma blindness by the year 2020. Most attention has focused on increasing the quantity of TT surgery performed, and large numbers of non-doctor operators have been trained to this end. Surgical audit by those performing TT surgery is not a routine part of any national trachoma control programme, and no effective mechanism exists for identifying surgeons experiencing poor outcomes. The authors propose a methodology for surgical audit at the level of the individual surgeon based on Lot Quality Assurance. Methods: A set number of patients operated on previously for upper eyelid TT are examined to detect the recurrence of TT. The number of recurrent cases found will lead to categorisation of the TT surgeon to either 'high recurrence' or 'low recurrence' with reasonable confidence. The threshold of unacceptability can be set by individual programmes according to previous local studies of recurrence rates or those from similar settings. Conclusions: Identification of surgeons delivering unacceptably high levels of recurrent TT will guide managers on the need for remedial intervention such as retraining.